Correlation of platelet indices with the spectrum of acute coronary syndrome and extent of coronary artery disease (Panacea Journal of Medical Sciences, 2022)
Introduction: Platelets have a major role in acute coronary syndrome and their activation is a hallmark of this. Troponin I, Troponin T and Creatine Kinase enzymes are not enough sensitive at an early stage of acute coronary syndrome. Platelet indices can be detected earlier, inexpensive, widely available and easily recordable in most clinical laboratories, thus could be a better marker in these patients. The primary objective of this study is to determine the correlation between platelet indices and spectrums of acute coronary syndrome or the number of vessels involved.Materialds and Methods: This is a prospective observation study conducted in a tertiary care teaching hospital of eastern India over a period of six months where 125 patients were non-randomly selected with a diagnosis of acute coronary syndrome who underwent coronary angiogram and reports correlated with platelet parameters.Results: A total of 100 patients were finally evaluated. Only platelet large cell ratio and platelet-crit were significantly higher in ST elevated myocardial infarction group compared to the unstable angina group. Across all the spectrums of acute coronary syndrome or extent of coronary artery disease there was a strong positive correlation within platelet distribution width, mean platelet volume and platelet large cell ratio, which was also very significant. Similarly total platelet count had a strong positive and very significant correlation with platelet-crit in the above groups.Conclusion: Increase platelet large cell ratio and platelet-crit seems to be independent risk factors for development of ST elevated myocardial infarct than unstable angina. Thus they could serve as simple but important early biomarkers for predicting development of ST elevated myocardial infarction compared to unstable angina in acute coronary syndrome patients.